A Study on The Awareness About the RTE Act, 2009 Among Teachers of Elementary Schools in Papumpare District - Phurpa Tsering Bappu,; Alok Singh Yadav, (International Journal of Scientific Research in Science and Technology, 2025)
It has become a basic right in India since the 2002 addition of the 86th amendment to our constitution. For this reason, children between the ages of 6 and 14 are legally required to receive quality national education free of charge. It is officially named RTE Act-2009. Understanding and using this Act is mainly the teacher’s role. For this reason, all teachers must learn about and follow the provisions of RTE Act-2009. In this paper, the researcher wanted to know how informed teachers are about the RTE Act-09. For this reason, the researcher took a total sample size of 70 from elementary teachers of Govt. and private schools in Papum Pare district of Arunacahl Pradesh. The study found that male and female teachers, teachers are belonging to urban areas, who are ware about RTE 2009 Act.
Keywords: RTE; Act; Govt; Private; School; Fundamental; Rights; Indian; Constitution; Awareness; level